Ways of improvement of system of setting of norms combustible of the wheeled machines of forces of guard of law and order - Сікоринський, Віталій Валерійович (Technology audit and production reserves, 2012)
transport. Certainly specific of the use of machines at implementation of officially-battle tasks. The ways of decision of this problem research of new methods of mathematical design of charges of fuel are offered for the wheeled machines of forces of guard of law and order